Soviet and East European Foreign Trade, 1946-1969 Statistical Compendium and Guide - Marer, Paul (Indiana University Press, 1972)
Soviet and East European Foreign Trade, 1946-1969: Statistical Compendium and Guide presents comprehensive data on the value of foreign trade of individual East European countries during the period 1946-69. The data are variously arranged in aggregative terms, by country or region of origin and destination, or by structure according to a number of commodity classifications.